Effects of Starch Type and Concentration on the Physicochemical, Rheological and Sensory Properties of Bream (Abramis brama L.) Surimi-Based Gels Enriched with β-1,3/1,6-D-Glucans - Bortnowska, Grażyna (Wpływ rodzaju i stężenia skrobi na właściwości fizykochemiczne, reologiczne i sensoryczne żeli przygotowanych z użyciem surimi z mięsa leszcza (Abramis brama L.) wzbogaconych dodatkiem β-1,3/1,6-D-glukanów, 2022)
The influence of starch type (waxy rice starch, WRS; tapioca starch, TS) and starch concentration (0-6%) on the physicochemical, rheological and sensory properties of surimi-starch gels (SSGs) enriched with b-1,3/1,6-D-Glucans was investigated. The main interactions of myofibrillar proteins were hydrophobic ones and disulfide bonds. The steady shear tests revealed that SSGs behaved as shear thinning fluids with yield stress and exhibited thixotropic properties. The SSGs showed temperature-dependent behaviour with activation energies: 27.5-9.04 kJ mol–1 and 27.5-6.47 kJ mol–1 regarding samples prepared with 0-6% WRS or TS, respectively. The structural differences between the SSGs were quantified in terms of the quality factor (Q), whose values at 10 Hz were in the following ranges: 6.64-20.3 and 6.64-29.1. The overall desirability index (ODI) values showed that the panelists most approved of the SSGs prepared with 5% TS and 6% WRS. The results presented in the work may be useful for producers and scientists involved in the design of pro-health foods.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 11-25
Keywords: surimi-starch-gels; β-1,3/1,6-D-Glucans; rheology; sensory analysis; surimi-skrobiowe żele; reologia; analiza sensoryczna